The Effect of Conservatism on Information Asymmetry - SRI HANIATI; FITRIANY FITRIANY (The Indonesian Journal of Accounting Research, 2013)
This study examines the influence of conservatism on information asymmetry. This research is conducted on non-financial companies, which were  listed on the BEI during 2007 to 2008. The conservatism was measured in some  models such as Givoly Hyan model (2000), Zhang model (2007), Kasznik model (1999), and market-based model (Duellman, 2006), whereas, asymmetrical accounting was measured with CSPREAD (Kanagaretnam etal.,2007). Zhang's model has the highest R2 (14.01%), and then followed by Givoly (2000) 13%, then others 11%. The research reveals that conservatism has a significant and negative correlation on information asymmetry. It supports Lafond and Watts (2006) which explains that conservatism has its role in reducing information asymmetry.This results suggest that IFRS should not abandon conservatism principles, because evidence shows that these principles reduce information asymmetry between managers and investors.